2021
DOI: 10.3390/f12040496
|View full text |Cite
|
Sign up to set email alerts
|

Soil Respiration in Alder Swamp (Alnus glutinosa) in Southern Taiga of European Russia Depending on Microrelief

Abstract: Swamp forests have been insufficiently studied yet in comparison with thoroughly examined carbon pools and greenhouse gas fluxes of peat bogs. This is primarily since the GHGs in swamp forests have huge spatial (due to the developed microrelief) and temporal variations (due to strong fluctuations in the groundwater level (GWL)). This significantly complicates their study, producing ambiguous results, especially in short-term field research. From June to October 2013–2016, we measured soil respiration (Rsoil) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Several studies in which total soil CO 2 efflux measurements were performed using a closed chamber system were selected for comparison ( Table 3 ). A study conducted in the boreal region of Russia reported that the total soil CO 2 efflux released from Histosols in black alder forests could be approximately 0.33 g CO 2 m −2 h −1 [ 36 ]. Another study performed in Finland reported that the annual total CO 2 efflux in less fertile forests was an average of 2000 g CO 2 m −2 y −1 , and an average of 3000 g CO 2 m −2 y −1 in fertile forests [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in which total soil CO 2 efflux measurements were performed using a closed chamber system were selected for comparison ( Table 3 ). A study conducted in the boreal region of Russia reported that the total soil CO 2 efflux released from Histosols in black alder forests could be approximately 0.33 g CO 2 m −2 h −1 [ 36 ]. Another study performed in Finland reported that the annual total CO 2 efflux in less fertile forests was an average of 2000 g CO 2 m −2 y −1 , and an average of 3000 g CO 2 m −2 y −1 in fertile forests [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…К сожалению, на территории России исследования потоков CH 4 и CO 2 из спорадических источников крайне ограничены (выполнялись разовые измерения без привязки к пространственной, сезонной и межгодовой изменчивости условий), причем проводились они в основном на территории Западной Сибири [Sabrekov et al, 2013;Mochenov et al, 2018;Glagolev et al, 2018;Terentieva et al, 2019] и европейской части России [Кузнецов и Бобкова, 2014;Иванов и др., 2018;Glukhova et al, 2021;Glukhova et al, 2022]. Вообще среднемасштабные (на уровне субъектов РФ) исследования болотных и лесных экосистем на территории России представлены далеко не во всех регионах, хотя вызывают особый интерес в силу возможности сохранения баланса между детальностью оценок и пространственно-временным охватом [Зацаринная и Волкова, 2011; Гришуткин и др., 2013; Баишева и др., 2015; Ильясов и др., 2019; Суслова, 2019], а инвентаризации, выполненные на территорию всей страны, требуют уточнения на региональном уровне [Вомперский и др., 2005].…”
Section: заболоченные леса как спорадические источники метанаunclassified
“…Потоки диоксида углерода в заболоченных лесах в целом слабо отличаются от величин, характерных для почв лесных экосистем, а относительная величина сезонной амплитуды сопоставима с таковой для метана в течение года. В целом полученные результаты оценки потоков в заболоченных лесах близки в сравнении с имеющимися литературными данными [Sabrekov et al, 2013;Mochenov et al, 2018;Glagolev et al, 2018;Terentieva et al, 2019;Glukhova et al, 2021;Glukhova et al, 2022].…”
Section: потоки Ch 4 и Co 2 и их инвентаризацияunclassified
“…The weighted average total soil methane fluxes in the study area were assessed based on the data on the representativeness of various microsites. The calculation was carried out according to the following formula (according to previous study [64]):…”
Section: Field Measurementsmentioning
confidence: 99%